Phenethyl isothiocyanate mediates autophagy via the AMPK/mTOR signal pathway in human glioblastoma multiforme cells - Shu-Fen Peng; Hsin-Chung Liu; Fu-Shin Chueh; Hsu-Tung Lee; Sheng-Yao Hsu; Jaw-Chyun Chen; Jing-Gung Chung; Yu-Cheng Chou (Toxicology and Applied Pharmacology, 2026)

Deciphering mechanisms of environmental adaptation, antibiotic tolerance, and potential virulence traits of Pseudomonas baetica isolated from anthropogenic habitat - Mu-Qi Zhang; Yi-Cheng Wang; Ming-Ying Mao; Yin-Qiu Qin; Peng Yan; Hui-Min Fu; Yuan-Xiang Mao; Ji-Cheng Liu; You-Peng Chen; Meng-Jiao Gao (Journal of Environmental Chemical Engineering, 2026)

Targeting microglial TLR3–NF-κB/MAPK and JAK/STAT Axis: PEITC as a suppressor of poly (I:C)-induced neuroinflammation - Yi-Ching Lan; Yan-Ru Xiao; Yow-Wen Hsieh; Yih-Dih Cheng; Shu-Fen Peng; Fu-Shin Chueh; Hsu-Tung Lee; Yu-Sheng Hsieh; Wei-Cheng Jiang; Wen-Tsong Hsieh; Yu-Cheng Chou (Toxicology and Applied Pharmacology, 2026)

Microplastics and decabromodiphenyl ethane co-exposure exerts antagonistic effects on microbial communities in a soil-earthworm system - Wenping Jiang; Mengru Fu; Tianzi Liu; Yanna Han; Cheng Peng; Wei Zhang (Journal of Hazardous Materials, 2026)

Evidence of beryllium isotope signatures in stratospheric air reveals long distance transport of micro/nano-plastics in the Southern Tibetan Plateau - Xuke Liu; Haogen Li; Yunchong Fu; Guohui Li; Peng Cheng; Guocheng Dong; Wen Liu (Journal of Hazardous Materials, 2026)

Annual energy use and economic performance of rice-based cropping systems: A three-year field study in Southwest China - Chuanhai Shu; Qingyue Cheng; Binbin Liu; Hongkun Xie; Yuanqing Shi; Mingming Hu; Hao Fu; Peng Ma; Na Li; Zhonglin Wang; Zongkui Chen; Yongjian Sun; et al. (Journal of Cleaner Production, 2026)

Exopolysaccharides from Enterococcus faecium alleviate cadmium damage in rice seedlings via regulating soil-root nitrogen metabolism - Min Zhong; Min Li; Chun-na Zhong; Zu-xuan Yan; Wei-fu Peng; Xin Cheng (Journal of Environmental Sciences, 2026)

Ecological and taxonomic significance of SEM‑based micromorphology in Gentiana (Gentianaceae) on the Qinghai‑Tibet Plateau - Ling Zheng; Yaqi Han; Xinyue He; Xiaoyu Zhou; Jingle Li; Peng-Cheng Fu (Flora, 2026)

Ultrahigh energy storage in BNBT-ST ceramics enabled by multiscale heterogeneous structures - Zhifei Zhang; Juntao Huang; Yuxin Xu; Saifei Wang; Guangyao Li; Chengchao Hu; Haihua Huang; Jigong Hao; Wei Li; Zhenxiang Cheng; Mahesh Kumar Joshi; Peng Fu (Chemical Engineering Journal, 2026)

Coordination-driven self-assembly of cerium-baicalein nanozyme promotes spinal cord injury repairing by simultaneously scavenging mitochondrial ROS and reprogramming macrophage polarization - Zhefan Xie; Cheng Peng; Xiaofeng Li; Yuqi Zhao; Shenghang Liu; Xuenian Ye; Yuxue Wang; Wenchong Tan; Huimin Hu; Jianqiang Li; Yanming Ma; Chunlai Fu (Chemical Engineering Journal, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Integrated NGS-MassARRAY Screening Reveals Hidden Wilson Disease Burden - Jia Tang; Hao Geng; Haihong Shi; Ting Yu; Jinping Qiao; Qingjiang Guo; Kun Wang; Jingjing Jiang; Qing Zhao; Na Nian; Yun Cheng; Shijing Wang; et al. (Phenomics, 2026)

Genesis of the Zhamuqin Pb−Zn−Ag polymetallic deposit in the middle-southern Great Xing’an Range, NE China: constraints from H−O−S−Pb isotope geochemistry and geochronology - Peng He; Man Li; Shuo Guo; Fei Teng; Xianyu Cheng; Qilong Fu (International Geology Review, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Dynamic cultivar-soil interactions drive accelerating genetic gains in a dryland wheat system - Yuan Li; Yong-He Zhu; He-Peng Lu; Neng Wang; Fu-Ying Cheng; Yan-Lei Du; Feng-Min Li (Field Crops Research, 2026)

Radiative cooling coatings and natural ventilation in urban street canyons: Synergies and trade-offs - Cheng-Peng Ma; Yu-Fei Tang; Shang-Xian Zhao; Gui-Xiong Yang; Fu-Yun Zhao; Yuguo Li; Rongpeng Zhang (Building and Environment, 2026)

VHL Suppresses Angiogenesis Through HIF-1a-Mediated Ang/Tie2/AMPK/VEGF Signaling Pathway in Tie-2 Expressed Macrophages (TEMs) - Min-Cheng Zou; Yu-Hao Yang; Yun-Peng Mao; Ya Liu; Hui-Bing Gao; Wen-Dong Liu; Jia Liu; Fu-Yong Zhang (Biochemical Genetics, 2026)

Species-specific accumulation and biomagnification of PFASs in aquatic and terrestrial organisms from the Xisha Islands - Yu-Quan Zhang; Jun Xiang; Jiao-feng Gu; Peng Zeng; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Li-cheng Wang; Hang Zhou; Ling Mo (Marine Pollution Bulletin, 2026)

Nitrogen inhibitors enhance ecosystem multifunctionality through microbial networks in alpine grasslands of the Tibetan Plateau - Fang-Kun Yang; Peng-Yang Wang; Ze-Yang Liu; Fu-Ying Niu; Cheng-Yi Xie; Yi-Ming Gao; Yan-Mei Ma; Yu-Xing Wang; Jia-Cheng Guo; Wen-Ying Wang (Applied Soil Ecology, 2026)

Evaluating the performance of coastal virtual stations from different combinations of altimetry missions - Fukai Peng; Zhong He; Xiaoli Deng; Ole Baltazar Andersen; Dapeng Mu; Yunzhong Shen; Yanguang Fu; Xiao Cheng (Advances in Space Research, 2026)

Seasonal temperature rise influences nitrous oxide and methane accumulation in freshwater habitats via distinctive microbial processes - Teng-Fei Ma; Wen-Ke Liu; Chong-Yang Xing; Ya-Song Chen; Hui-Min Fu; Ji-Chun Bai; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Meng-Wen Peng (Environmental Pollution, 2026)

Metabolic Engineering of Selenocysteine Biosynthesis and Insertion Pathway in Lactococcus Lactis - Jing-Jing Peng; Yao Qin; Shi-Yang Yue; Ping Shi; Ling-Yu Wang; Chen-Xing Liu; Yu-Hui Fang; Xiao-Dong Pei; Fu-Tian Yu; Xin-Bi Huang; Xiao-Ling Liu; Cheng-Hua Wang (Biological Trace Element Research, 2026)

Optimizing the yield-quality balance in wheat by enhancing N uptake and allocation through split N application at the booting stage - Wei Wu; Yang Wang; Huasen Xu; Boyang Fu; Zhengping Peng; Christoph-Martin Geilfus; Cheng Xue (Field Crops Research, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Polycrystalline ferroelectricity in a molecular crystal for piezoelectric sensing - Gele Teri; Jing-Song Tang; Peng-Cheng Zhuge; Jia-Qi Luo; Hao-Fei Ni; Lei Pan; Qiang-Qiang Jia; Yi Zhang; Da-Wei Fu; Zhi-Xu Zhang (Chemical Engineering Journal, 2026)

Hydrated salt composites with binary carbon networks and laser-treated hydrophobic surfaces for multifunctional outdoor building thermal management - Yizhe Liu; Weizheng Cheng; Yangzhe Xu; Modi Jiang; Benwei Fu; Chengyi Song; Wen Shang; Peng Tao; Tao Deng (Chemical Engineering Journal, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Experimental study on hydrodynamic characteristics of mussel-fouled nets under current and its application in numerical simulation - Tianhu Cheng; Yuwang Xu; Shixiao Fu; Yunqiang Peng; Zhentao Jiang (Aquaculture, 2026)

Ascertaining and optimizing bearing performance for deformed shield tunnels reinforced with epoxy-bonded steel plates - Zhiwei Zhang; Xuesong Cheng; Tianqi Zhang; Hao Fu; Liyang Qi; Tao Cui; Peng Zhang; Gang Zheng (Tunnelling and Underground Space Technology, 2026)

Efficient degradation of sulfamethoxydiazine by a CuO/sulfite/O2 system: Mechanism insight and environmental applicability - Peng Cheng; Ziwei Zhang; Jiawei Jiang; Jing Sun; Tengfei Fu; Feng Wu (Journal of Water Process Engineering, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Computer vision-assisted sorting and selective cultivation of high-activity anammox granules - Shi-Jun Li; Haoran Li; Hui-Min Fu; Yi-Cheng Wang; Xun Weng; Wei Wang; You-Peng Chen (Water Research, 2026)

Incomplete lineage sorting, hybridization and polyploidization blurred phylogenetic relationships of gentians from the Qinghai-Tibetan Plateau - Shan-Shan Sun; Shu-Han Xu; Wen-Jie Yi; Shi-Long Chen; Pan Li; Daiki Takahashi; Harue Abe; Xiao-Lei Ma; Peng-Cheng Fu (Molecular Phylogenetics and Evolution, 2026)

Hybridization and incomplete lineage sorting characterize the evolutionary history of two East Asian clades of Stewartia (Theaceae) - Han-Yang Lin; Miao Sun; Jian-Jun Jin; Cheng-Xin Fu; Douglas E. Soltis; Pamela S. Soltis; Yun-Peng Zhao (Molecular Phylogenetics and Evolution, 2026)

Nickel isotopic evidence for potential deep magmatic sulfide ore bodies in orogenic settings - Peng-Yi Li; Shui-Jiong Wang; Fu-Ping Pei; Guan-Wen Yu; Bing-Qian Ding; Zi-Cheng Guan; Kai Song; Wen-Liang Xu (Geochimica et Cosmochimica Acta, 2026)

Anammox community characteristics and stable relationships centered on anammox bacteria - Yi-Cheng Wang; Hui-Min Fu; Hong-Yuan Liu; Han Wu; Zi-Han Zeng; Jian-Hong He; Meng-Jiao Gao; Peng Yan; Liang Zhang; You-Peng Chen (Chemical Engineering Journal, 2026)

Corrigendum to “Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk” [Toxicology and Applied Pharmacology Volume 503, October 2025, 117465]. - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Tailoring anchoring functionalities of self-assembled materials for efficient wide-bandgap perovskite solar cells - Zhong-En Shi; Yu-Fan Fu; Bo-Shun Peng; Ting-Chun Hung; Deebakkrishnan Ganesan; Rajendiran Balasaravanan; Shao-Huan Hong; Cheng-Liang Liu; Chun-Jen Su; Ming-Chou Chen; Chih-Ping Chen (Chemical Engineering Journal, 2025)

How the Carbon Neutrality Process Moves Forward: a Global-scale Evaluation from Past To Future - Yicheng Yang; Zefeng Qi; Hongxuan Fu; Shuan Peng; Nihed Benani; Xi Cheng; Jian Lin Chen; Pingjian Yang; Guozhu Mao (International Journal of Environmental Research, 2025)

Transcriptomic profiling reveals mechanism, therapeutic potential, and prognostic value of cancer stemness characteristic in nasopharyngeal carcinoma - Jin-Wei Chen; Run-Nan Shen; Jiang-Quan Zhu; Ying-Hang Wang; Liang-Min Fu; Yu-Hang Chen; Jia-Zheng Cao; Jin-Huan Wei; Jun-Hang Luo; Jia-Ying Li; Cheng-Peng Gui (Functional & Integrative Genomics, 2025)

Ultrasonic high efficiency preparation of arctigenin from the fruits of Arctium lappa L using Aspergillus niger with deep eutectic solvent assisted - Yubin Ren; Shuang Jin; Weili Liu; Cailiang Peng; Hongyao Cai; Huayong Zhao; Yupeng Cheng; Yujie Fu; Na Zhang; Siyuan Wang; Chen Lv (Biotechnology Letters, 2025)

Per- and polyfluoroalkyl substances in tissues of intermediate egrets (Ardea intermedia) from the South China Sea - Ling Mo; Jun Xiang; Ming-Yang Wang; Yu-Quan Zhang; Qin-Wei Hao; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Jing Zheng; Qiao Xing; Bin Tang; Li-Cheng Wang (Marine Pollution Bulletin, 2025)

Microplastics: an overlooked particle organic carbon in river systems - Xuke Liu; Weijian Zhou; Peng Cheng; Fei Zhang; Liangcheng Tan; Yunchong Fu; Yukun Fan; Jianghu Lan; Huachun Gu; Wen Liu; Ting Wang (Science Bulletin, 2025)

In vitro assessment of dermal penetration and skin barrier impairment by per- and polyfluoroalkyl substances (PFASs) from consumer products - Xuan Zhao; Yanna Han; Mengru Fu; Shanqi Zhou; Yuhe Yang; Wenyue Zhang; Cheng Peng; Wei Zhang; Qingqing Li; Qinghe Zhu; Jie Yang (Environmental Pollution, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Efficient catalytic decomposition of N2O over neodymium-modified Co3O4 catalysts - Dongxin Yao; Shuang Cao; Piaopiao Wei; Peng Zhang; Fang Cheng; Yaxiong Zeng; Hailu Fu; Zhongbiao Wu (Chemical Engineering Journal, 2025)

The critical role of OsYTH10 in promoting early flowering of rice under long sunlight - Jun Yang; Zhihao Chen; Peng Wang; Mvuyeni Nyasulu; Qin Cheng; Xiaopeng He; Jie Xu; Junru Fu; Dahu Zhou; Linjuan Ouyang; Haohua He; Jianmin Bian (Theoretical and Applied Genetics, 2025)

A novel multifunctional suction-controlled apparatus for investigating tensile strength of unsaturated soils - Xiang-Shen Fu; Han-Lin Wang; Ren-Peng Chen; Cheng-Shuang Yin; Yue-Hui Sun; Xiao-Hu Zhang; Daniel Dias (Transportation Geotechnics, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

OC7 phase I: Toward practical sea-state-dependent modeling of hydrodynamic viscous drag and damping - Lu Wang; Amy Robertson; Jason Jonkman; Yingqian Liao; Petter Andreas Berthelsen; Serag-Eldin Abdelmoteleb; Peter Rohrer; Vishnu Ramachandran Nair Rajasree; Erin Bachynski-Polić; Constance Clement; Cédric Le Cunff; Prokopios Vlachogiannis; et al. (Ocean Engineering, 2025)

Comprehensive identification of crucial biomarkers and therapeutic targets in cholestasis via integrated single-cell RNA and transcriptome sequencing analysis - Cichun Wu; Da Cheng; Juan Mo; Nianqi Zhou; Shifang Peng; Lei Fu (Mammalian Genome, 2025)

Establishment of an efficient in vitro regeneration protocol for Dendrobium primulinum Lindl. by one-step seedling formation - Cheng-Li Liu; Jie-Mei Deng; Shun Peng; Heng-Yu Huang; Fu-Rong Xu (In Vitro Cellular & Developmental Biology - Plant, 2025)

Establishment of Agrobacterium-mediated genetic transformation and CRISPR/Cas9-guided gene editing in Elymus nutans - Cheng Li; Xiaomei Peng; Zhengshe Zhang; Yaling Liu; García-Caparrós Pedro; Chunxiang Fu; Yongping Yang; Quanmin Dong; Yuanwen Duan; Xudong Sun (Journal of Plant Physiology, 2025)

Numerical study of the hydrodynamic load of a fish net considering the effects of diffraction waves - Tianhu Cheng; Shixiao Fu; Yuwang Xu; Yunqiang Peng; Zhentao Jiang (Ocean Engineering, 2025)

Microbial metabolism in wormcast affected the perturbation on soil organic matter by microplastics under decabromodiphenyl ethane stress - Yanna Han; Mengru Fu; Yuhe Yang; Zhiyin Zhang; Tianzi Liu; Shanqi Zhou; Zhihua Qiao; Gehui Wang; Cheng Peng; Wei Zhang (Journal of Hazardous Materials, 2025)

Composite of mixed-cation perovskite MA1-FA PbI3 with MoSe2 for enhanced photocatalytic H2 evolution - Hui Fu; Qianqian Zhang; Yaqiang Wu; Zeyan Wang; Yuanyuan Liu; Zhaoke Zheng; Hefeng Cheng; Baibiao Huang; Peng Wang (Chemical Engineering Journal, 2025)

Two new phenolic glycosides from Cyathula officinalis and their relaxant effects on uterine smooth muscle - Mei-Ji Sun; Rui Zhao; Min Wen; Chun-Wang Meng; Hai-Guo Su; Fu-Xin Mi; Cheng Peng; Juan Liu; Liang Xiong (Phytochemistry Letters, 2025)

Cold stress changes the intestinal oxidative stress-mediated MAPK pathways and lipid metabolism in Takifugu fasciatus - Yuxi Liu; Xuechun Zang; Cheng Zhao; Peng Chu; Heyu Chen; Dongyong Fu; Sijin Wang; Kai Zhang; Tao Wang; Shaowu Yin (Aquaculture, 2025)

Molecular composition difference of electron donating moieties between natural organic matter and effluent organic matter probed by chlorine dioxide - Quan Gao; Yanheng Pan; Yangjian Zhou; Jianglin Peng; Qingqing Kong; Yanhui Cheng; Qing-Long Fu; Xin Yang (Water Research, 2025)

Transcriptional and molecular simulation analysis of the response mechanism of anammox bacteria to 3,4-dimethylpyrazole phosphate stress - Cui-Zhong Chen; Jin Wang; Yi-Cheng Wang; Hui-Min Fu; Xiao-Wei Xu; Peng Yan; You-Peng Chen (Journal of Hazardous Materials, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Aiding and opposing cooling the street canyon through trees and water bodies: Conflicting effects from temperature reduction and ambient humidification - Ming Yang; Cheng-Peng Ma; Shang-Xian Zhao; Fu-Yun Zhao; Jiang-Hua Guo (Building and Environment, 2025)

Electrochemical upcycling strategy for polyethylene terephthalate plastic coupled with efficient hydrogen production - Xingye Lu; Yuhao Guo; Hui Fu; Jia Song; Congcong Liang; Hechun Jiang; Zeyan Wang; Yuanyuan Liu; Hefeng Cheng; Zhaoke Zheng; Yaqiang Wu; Peng Wang; et al. (Chemical Engineering Journal, 2025)

Efficient and green preparation of baicalein from Radix scutellariae with deep eutectic solvent pretreated bioconversion of cellulose-based microreactor - Shuang Jin; Yubin Ren; Yupeng Cheng; Weili Liu; Cailiang Peng; Bingyou Yang; Haixue Kuang; Yujie Fu; Chen Lv; Hongyao Cai (Sustainable Chemistry and Pharmacy, 2024)

Manganese(III) dominants the mobilization of phosphorus in reducing sediments: Evidence from Aha reservoir, Southwest China - Quan Chen; Jing-fu Wang; Meng-qiang Zhu; Hai-bo Qin; Peng Liao; Zhi-tong Lu; Peng-cheng Ju; Jing-an Chen (Science of The Total Environment, 2024)

Targeted investigation of per- and polyfluoroalkyl substances from domestic cosmetics and personal care products in China and its implications for human exposure - Xuan Zhao; Mengru Fu; Shanqi Zhou; Yanna Han; Wei Zhang; Cheng Peng; Qingqing Li; Qinghe Zhu; Jie Yang (Science of The Total Environment, 2024)

Metabolomics integrated with mass spectrometry imaging reveals novel action of tetramethylpyrazine in migraine - Ziwei Xing; Yu Chen; Junren Chen; Cheng Peng; Fu Peng; Dan Li (Food Chemistry, 2024)

Low-grade systemic inflammation links heavy metal exposures to mortality: A multi-metal inflammatory index approach - Yin Wang; Yuyan Wang; Ruizhen Li; Baiwen Ni; Ruixin Chen; Yun Huang; Rongrong Cheng; Pei Li; Han Li; Yang Peng; Xue Chen; Jingyu Wang; et al. (Science of The Total Environment, 2024)

Contamination characteristics and dietary intake risk of brominated flame retardants in fishes around a typical e-waste dismantling site in Southern China - Shanqi Zhou; Zhihua Qiao; Siyuan Ling; Mengru Fu; Yanna Han; Cheng Peng; Wei Zhang; Juying Lei (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Genesis of high-Al chromitites from Xiaosuihe peridotite (Central Jilin Province, NE China): Implication for initial subduction of the Paleo-Asian ocean - Bing-Qian Ding; Fu-Ping Pei; Jing-Yang Wei; Jin-Rui Zhang; Zi-Cheng Guan; Kai Song; Tian-Jiao Sang; Peng-Yi Li (Lithos, 2024)

Rock-physics modeling and pre-stack seismic inversion for the Cambrian superdeep dolomite reservoirs in Tarim Basin, Northwest China - Shi-Kai Jian; Li-Yun Fu; Wensheng Duan; Gengxin Peng; Suo Cheng; Yongliang Tang; Duoming Zheng (Marine and Petroleum Geology, 2024)

Corrigendum to “2′-O-galloylhyperin attenuates LPS-induced acute lung injury via upregulation antioxidation and inhibition of inflammatory responses in vivo” [Chem. Biol. Interact. 304 (1 May 2019) 20–27] - Sun-Dong Zhang; Peng Wang; Jing Zhang; Wei Wang; Li-Ping Yao; Cheng-Bo Gu; Thomas Efferth; Yu-Jie Fu (Chemico-Biological Interactions, 2024)

Converting fruit peels into biodegradable, recyclable and antimicrobial eco-friendly bioplastics for perishable fruit preservation - Shikai Zhang; Xinxin Cheng; Wenjing Yang; Quanbin Fu; Feng Su; Peng Wu; Yijing Li; Fen Wang; Houshen Li; Shiyun Ai (Bioresource Technology, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Correction to: Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao‑Bo Li; Yan‑Xun Han; Zi‑Yue Fu; Yu‑Chen Zhang; Min Fan; Shu‑Jia Sang; Xi‑Xi Chen; Bing‑Yu Liang; Yu‑Chen Liu; Peng‑Cheng Lu; Hua‑Wei Li; Hai‑Feng Pan; et al. (Environmental Science and Pollution Research, 2024)

Five coexisting brominated flame retardants in a water-sediment-Vallisneria system: Bioaccumulation and effects on oxidative stress and photosynthesis - Mengru Fu; Zhihua Qiao; Shanqi Zhou; Yanna Han; Siyuan Ling; Cheng Peng; Wei Zhang; Jinhong Wu (Science of The Total Environment, 2024)

Co-exposure of decabromodiphenyl ethane and cadmium increases toxicity to earthworms: Enrichment, oxidative stress, damage and molecular binding mechanisms - Zhihua Qiao; Xinlin Sun; Mengru Fu; Shanqi Zhou; Yanna Han; Xuan Zhao; Kailin Gong; Cheng Peng; Wei Zhang; Fang Liu; Chunmei Ye; Jie Yang (Journal of Hazardous Materials, 2024)

Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao-Bo Li; Yan-Xun Han; Zi-Yue Fu; Yu-Chen Zhang; Min Fan; Shu-Jia Sang; Xi-Xi Chen; Bing-Yu Liang; Yu-Chen Liu; Peng-Cheng Lu; Hua-Wei Li; Hai-Feng Pan; et al. (Environmental Science and Pollution Research, 2024)
Air pollution can cause disease and has become a major global environmental problem. It is currently believed that air pollution may be related to the progression of SSNHL. As a rapidly developing city in recent years, Hefei has serious air pollution. In order to explore the correlation between meteorological variables and SSNHL admissions, we conducted this study. This study investigated the short-term associations between SSNHL patients admitted to the hospital and Hefei climatic variables. The daily data on SSNHL-related hospital admissions and meteorological variables containing mean temperature (T-mean; °C), diurnal temperature range (DTR; °C), atmospheric pressure (AP; Hp), and relative humidity (RH; %), from 2014 to 2021 (2558 days), were collected. A time-series analysis integrating distributed lag non-linear models and generalized linear models was used. PubMed, Embase, Cochrane Library, and Web of Science databases were searched. Literature published up to August 2023 was reviewed to explore the potential impact mechanisms of meteorological factors on SSNHL. The mechanisms were determined in detail, focusing on wind speed, air pressure, temperature, humidity, and air pollutants. Using a median of 50.00% as a baseline, the effect of exceedingly low T-mean in the single-day hysteresis effect model began at a lag of 8 days (RR = 1.032, 95% CI: 1.001 ~ 1.064). High DTR affected the admission rate for SSNHL on lag 0 day. The significance of the effect was the greatest on that day (RR = 1.054, 95% CI: 1.007 ~ 1.104) and then gradually decreased. High and exceedingly high RH affected the admission rate SSNHL on lag 0 day, and these effects lasted for 8 and 7 days, respectively. There were significant associations between all grades of AP and SSNHL. This is the first study to assess the effect of meteorological variables on SSNHL-related admissions in China using a time-series approach. Long-term exposures to high DTR, RH values, low T-mean values, and all AP grades enhance the incidence of SSNHL in residents. Limiting exposure to extremes of ambient temperature and humidity may reduce the number of SSNHL-related hospital visits in the region. It is advisable to maintain a suitable living environment temperature and avoid extreme temperature fluctuations and high humidity. During periods of high air pollution, it is recommended to stay indoors and refrain from outdoor exercise.

Pectin-based film activated with carboxylated cellulose nanocrystals-stabilized oregano essential oil Pickering emulsion - Wenjing Yang; Shikai Zhang; Yanna Hu; Quanbin Fu; Xinxin Cheng; Yijing Li; Peng Wu; Houshen Li; Shiyun Ai (Food Hydrocolloids, 2024)

Biosynthetic potential of uncultured anammox community bacteria revealed through multi-omics analysis - Yi-Cheng Wang; Hui-Min Fu; Yu Shen; Jin Wang; Nuo Wang; You-Peng Chen; Peng Yan (Bioresource Technology, 2024)

Reactive Oxygen Species-Mediated Mitophagy and Cell Apoptosis are Involved in the Toxicity of Aluminum Chloride Exposure in GC-2spd - Hui- xin Peng; Fu Chai; Ke-heng Chen; Yan-xin Huang; Guang-ji Wei; Huixiong Yuan; Yan-fang Pang; Shi-hua Luo; Chun-fang Wang; Wen-cheng Chen (Biological Trace Element Research, 2024)

New insights into functional divergence and adaptive evolution of uncultured bacteria in anammox community by complete genome-centric analysis - Yi-Cheng Wang; Yanping Mao; Hui-Min Fu; Jin Wang; Xun Weng; Zi-Hao Liu; Xiao-Wei Xu; Peng Yan; Fang Fang; Jin-Song Guo; Yu Shen; You-Peng Chen (Science of The Total Environment, 2024)

Garnet and zircon petrochronology reveal coherent subduction and exhumation of eclogites and associated schists in the Changning–Menglian orogenic belt, southeast Tibet - Ying Zhou; Hao Cheng; Zhi-min Peng; Yu-zhen Fu; Kai-Yang Du (Lithos, 2024)

Corrigendum to “Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients” [J. Trace Elem. Med. Biol. 83 (2024) 127415] - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Novel material to enhance the integrity of CCUS cement sheath: Exploration and application of calcium aluminate cement - Peng Gong; Huacai Fu; Dan He; Yuanpeng Wu; Kaiyuan Mei; Chunmei Zhang; Xin He; Tao Liu; Shangdong Li; Xiaowei Cheng (Gas Science and Engineering, 2024)

Motility behavior and physiological response mechanisms of aerobic denitrifier, Enterobacter cloacae strain HNR under high salt stress: Insights from individual cells to populations - Meng Cheng; Hui-Min Fu; Zheng Mao; Peng Yan; Xun Weng; Teng-Fei Ma; Xiao-Wei Xu; Jin-Song Guo; Fang Fang; You-Peng Chen (Science of The Total Environment, 2024)

Holocene temperature and cold events recorded in arid Central Asian peatlands - Haiyan Zhao; Weijian Zhou; Peng Cheng; Xuefeng Yu; Yubin Wu; Peixian Shu; Feng Xian; Hua Du; Jie Zhou; Guoqing Zhao; Yukun Fan; Yunchong Fu; et al. (Quaternary Science Reviews, 2024)

Radiocarbon chronology of sediments with implications for climatic events in Lop Nur, NW China - Yuda Chui; Weijian Zhou; Peng Cheng; Ling Yang; Xingxing Liu; Jianghu Lan; Guoqing Zhao; Shugang Wu; Yunchong Fu; Xiaohu Xiong; Wei Gong (Journal of Asian Earth Sciences, 2024)

Enhanced removal of Cd2+ from water by a bacterioferritin from Candidatus Kuenenia stuttgartiensis within engineering bacteria - Jin Wang; Cui-Zhong Chen; Yi-Cheng Wang; Hui-Min Fu; Peng Yan; You-Peng Chen (Chemical Engineering Journal, 2024)

Stability analysis of intermittently jointed rock slopes based on the stepped failure mode - Dejian Li; Junwen Fu; Hekai Li; Xiao Cheng; Lianheng Zhao; Yingbin Zhang; Xinyan Peng (Journal of Mountain Science, 2024)

Insights into the performance and mechanism of Cr(VI) and U(VI) removal in water using innovative cross-linked chitosan adsorbent - Peng Cheng; Zhiyang Wei; Yara Arbid; Tengfei Fu; Xiaowei Liu; Olivier Monfort (Journal of Environmental Chemical Engineering, 2024)

Corrigendum to “Procyanidin B2: A promising multi-functional food-derived pigment for human diseases” [Food Chem. 420 (2023) 136101] - Junren Chen; Kexin Zhong; Yiqi Jing; Shengmeng Liu; Siqi Qin; Fu Peng; Dan Li; Cheng Peng (Food Chemistry, 2024)

Effect of long-term straw return on organic matter transformation by hydroxyl radical during paddy soil oxygenation - Yanqi Xiao; Wei Peng; Junhong Fu; Yaqi Ning; Hao-jie Cui; Dong Cheng; Na Zhang; Weijun Zhou; Wenjuan Liao (Chemical Engineering Journal, 2024)

Rheumatoid arthritis is a protective factor against Alzheimer’s disease: a bidirectional two-sample Mendelian randomization study - Guo-Shuai Li; Yong-Ze Yang; Guo-Rong Ma; Peng-Fei Li; Qing-Hao Cheng; An-Ren Zhang; Zhuang-Zhuang Zhang; Fu-Kang Zhang; Xin Yang; Hua Fan; Hong-Zhang Guo (Inflammopharmacology, 2024)

Enhancing flame retardancy, mechanical durability, and anti-aging property of polyurethane foam via novel cyclic phosphonate - Zhi-Cheng Fu; Fa-Yang Bu; Zhe-Peng Li; Ting Wang; Jin-Ni Deng; Hai-Bo Zhao; Sheng-Chao Huang; Yu-Zhong Wang; Ming-Jun Chen (Chemical Engineering Journal, 2024)

Chronic cold environment regulates rheumatoid arthritis through modulation of gut microbiota-derived bile acids - Juan Liu; Fu Peng; Hao Cheng; Dandan Zhang; Yuxi Zhang; Lixia Wang; Fei Tang; Jing Wang; Yan Wan; Jing Wu; Yinlin Zhou; Wuwen Feng; et al. (Science of The Total Environment, 2023)

Toxicity of decabromodiphenyl ethane on lettuce: Evaluation through growth, oxidative defense, microstructure, and metabolism - Zhihua Qiao; Xinlin Sun; Kailin Gong; Xiuping Zhan; Kailun Luo; Mengru Fu; Shanqi Zhou; Yanna Han; Yuyou He; Cheng Peng; Wei Zhang (Environmental Pollution, 2023)

Mitochondrial dysfunction: a new molecular mechanism of intervertebral disc degeneration - Chao Song; Yulin Xu; Qinghua Peng; Rui Chen; Daqian Zhou; Kang Cheng; Weiye Cai; Tao Liu; Chenyi Huang; Zhijiang Fu; Cong Wei; Zongchao Liu (Inflammation Research, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Long-term anthropogenic field management enhanced wheat productivity and resource utilization in the Loess Plateau region of China - Peng Wu; Gang Zhao; Qi Wu; Hua Huang; Peng Zhang; Kemoh Bangura; Jianfu Xue; Min Sun; Shangzhong Li; Lei Wang; Wanli Cheng; Jian Fu; et al. (European Journal of Agronomy, 2023)

Effect of the inoculation of Phanerochaete chrysosporium on nitrogen migration and organic matter conversion during electrolytic manganese residue composting - Xiangyu Peng; Ming Yan; Qingqing Xie; Lan Gao; Xiaojuan Pu; Yukui Fu; Hanwen Liu; Min Cheng; Piao Xu; Danlian Huang; Lin Tang (Bioresource Technology, 2023)

Species diversity and related ecology of chiggers on small mammals in a unique geographical area of Yunnan Province, southwest China - Yu Guo; Juan-Xiu Zhou; Xian-Guo Guo; Wen-Yu Song; Cheng-Fu Zhao; Zhi-Wei Zhang; Rong Fan; Ting Chen; Yan Lv; Peng-Wu Yin; Dao-Chao Jin (Experimental and Applied Acarology, 2023)

Pectin-nanolignin composite films with water resistance, UV resistance, and antibacterial activity - Shikai Zhang; Xinxin Cheng; Quanbin Fu; Yijing Li; Peng Wu; Yiheng Qiao; Jianfeng Yan; Lin Si; Geoffrey I.N. Waterhouse; Houshen Li; Shiyun Ai (Food Hydrocolloids, 2023)

Contamination characteristics and potential health risk of brominated flame retardants in paddy soils and rice plants around a typical e-waste recycling site in south China - Kailun Luo; Zhihua Qiao; Weiyu Liang; Cong Lu; Mengru Fu; Shanqi Zhou; Yanna Han; Cheng Peng; Wei Zhang (Environmental Pollution, 2023)

Acrylonitrile butadiene styrene microplastics aggravate the threat of decabromodiphenyl ethane to Eisenia fetida: Bioaccumulation, tissue damage, and transcriptional responses - Mengru Fu; Jiaqi Tan; Shanqi Zhou; Peng Liu; Zhihua Qiao; Yanna Han; Wei Zhang; Cheng Peng (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Procyanidin B2: A promising multi-functional food-derived pigment for human diseases - Junren Chen; Kexin Zhong; Yiqi Jing; Shengmeng Liu; Siqi Qin; Fu Peng; Dan Li; Cheng Peng (Food Chemistry, 2023)

Experiment study on reactive powder concrete beams using spirals reinforcement under torsion - Xia Cao; Yong-peng Quan; Yi-cheng Ren; Feng Fu; Qi-zhi Jin; Da-bo He; Yan Zheng (Engineering Structures, 2023)

Tidal variation modulates the dissolved silicate behavior and exchange flux across the semi-enclosed bay‐coastal water continuum, China - Peng Zhang; Jiale Xie; Jibiao Zhang; Miaojian Fu; Weisheng Luo; Mingyue Cheng (Frontiers in Marine Science, 2023)
Coastal water is the key transition zone for the circulation and transport of nutrients. Their role in transporting nutrients is important to understanding global dissolved silicate (DSi) cycles and sources of nutrients supporting the biological pump and ocean carbon cycle. However, the understanding of controlling DSi exchange flux between the semi-enclosed bay and coastal water was still scarcely due to limitations in continuous observation. In this study, we conducted continuous investigations during spring tide (ST) and neap tide (NT) in 2021 in Shuidong Bay (SDB), China, to explore the impacts of different tidal cycles on DSi in SDB and the fluxes across SDB and South China Sea (SCS) coastal water. The findings demonstrated that there were significant differences in DSi concentrations and nutrients ratios between ST and NT in S1 station ( P < 0.05 ). In addition, the DSi concentrations were 32.01 ± 27.21 μmol/L and 51.48 ± 48.44 μmol/L in ST and NT, respectively. Besides, the net export of DSi from SDB to SCS was 0.18 t throughout the entire early of autumn tidal cycle, suggesting SDB was the source of DSi, and its behavior across the semi-enclosed bay‐coastal water continuum was largely controlled by tidal characteristics (tidal height, flow velocity), water physicochemical parameters (salinity, pH), biological uptake and terrestrial sources input. SDB in ST has higher proportions of DSi: DIN (dissolved inorganic nitrogen) (1.49 ± 1.28) and DSi: DIP (dissolved inorganic phosphorus) (58.6 ± 43.73) compared with NT, DSi: DIN and DSi: DIP for the NT period were 1.45 ± 1.15 and 43.99 ± 28.59, indicating that phosphorus (P) is the limiting trophic factor for SDB. The tidal cycle in SDB would alter the DSi stoichiometry and mitigated the impact of eutrophication caused by terrestrial sources. This study provides new insights in the Si tidal cycling across the semi-enclosed bay‐coastal water continuum, which was implications for understanding DSi biogeochemical process and primary production dynamics in coastal water.

Legacy and novel brominated flame retardants in a lab-constructed freshwater ecosystem: Distribution, bioaccumulation, and trophic transfer - Shanqi Zhou; Mengru Fu; Siyuan Ling; Zhihua Qiao; Kailun Luo; Cheng Peng; Wei Zhang; Juying Lei; Bingsheng Zhou (Water Research, 2023)

Response mechanism of lettuce (Lactuca sativa L.) under combined stress of Cd and DBDPE: An integrated physiological and metabolomics analysis - Zhihua Qiao; Kailun Luo; Shanqi Zhou; Mengru Fu; Xuechun Shao; Kailin Gong; Cheng Peng; Wei Zhang (Science of The Total Environment, 2023)

Genomic analysis of Marinomonas algicola SM1966T reveals its role in marine sulfur cycling - Min Zhang; Xiao-Di Wang; Yue Lin; Shu-Yan Wang; Shan Zhang; Jin Cheng; Mei-Ling Sun; Peng Wang; Hui-Hui Fu; Chun-Yang Li; Nan Zhang (Marine Genomics, 2023)

3D-printed stretchable sensor based on double network PHI/PEDOT:PSS hydrogel annealed with cosolvent of H2O and DMSO - Xiu-Yan Cheng; Shu-Qiang Peng; Li-Xin Wu; Qing-fu Sun (Chemical Engineering Journal, 2023)

Biochar supported nanoscale zero-valent iron for the kinetics removal and mechanism of decabromodiphenyl ethane in the sediment - Cong Lu; Xuan Zhao; Zhihua Qiao; Kailun Luo; Shanqi Zhou; Mengru Fu; Cheng Peng; Wei Zhang (Environmental Science and Pollution Research, 2023)

Repeated exposure causes different bioaccumulation and biotoxicity of decabromodiphenyl ethane in earthworms compared to one step exposure - Mengru Fu; Xuan Zhao; Shanqi Zhou; Peng Liu; Zhihua Qiao; Yanna Han; Kailin Gong; Cheng Peng; Wei Zhang; Jinhong Wu (Process Safety and Environmental Protection, 2023)

The Intrinsic Relation between the Hydrogel Structure and In Vivo Performance of Hyaluronic Acid Dermal Fillers: A Comparative Study of Four Typical Dermal Fillers - Weiwei Zhou; Shuai Hou; Shu Deng; Yang Peng; Wei Fu; Yang Zhou; Jie Yang; Cheng Peng (Tissue Engineering and Regenerative Medicine, 2023)

Plow layer management during the fallow season can enhance the wheat productivity and resource utilization in a semi-arid region - Gang Zhao; Peng Wu; Fu Liu; Shangzhong Li; Jianjun Zhang; Yi Dang; Lei Wang; Shuying Wang; Wanli Cheng; Tie Cai; Tinglu Fan (Soil and Tillage Research, 2023)

Apoptosis-related long non-coding RNA LINC5438 of Bombyx mori promotes the proliferation of BmNPV - Peng Chen; Min Cai; Yu-Jie Feng; Cong Li; Zhan-Qi Dong; Wen-Fu Xiao; Liang Tang; Yan Zhu; Ting Tian; Bo-Yuan Deng; Min-Hui Pan; Cheng Lu (Pesticide Biochemistry and Physiology, 2023)

Salvia miltiorrhiza polysaccharide and its related metabolite 5-methoxyindole-3-carboxaldehyde ameliorate experimental colitis by regulating Nrf2/Keap1 signaling pathway - Yu-Ping Fu; Xi Peng; Chao-Wen Zhang; Quan-Xing Jiang; Cen-Yu Li; Berit Smestad Paulsen; Frode Rise; Chao Huang; Bin Feng; Li-Xia Li; Xing-Fu Chen; Ren-Yong Jia; et al. (Carbohydrate Polymers, 2023)

Cesium exposure and pulmonary function decline: Potential mediating role of oxidative stress in chronic obstructive pulmonary disease patients - Min-Min Tang; Xue-Feng Hou; Jing Sun; Jia-Yi Cheng; You-Peng Deng; Meng-Die Li; Ling Liu; Dong-Xu Hua; Jin Yang; Ya-Lin Jiang; Lin Fu; Hui Zhao (Atmospheric Pollution Research, 2023)

Polylactic acid microplastics induce higher biotoxicity of decabromodiphenyl ethane on earthworms (Eisenia fetida) compared to polyethylene and polypropylene microplastics - Yanna Han; Mengru Fu; Jinhong Wu; Shanqi Zhou; Zhihua Qiao; Cheng Peng; Wei Zhang; Fang Liu; Chunmei Ye; Jie Yang (Science of The Total Environment, 2023)

Evidence of aircraft activity impact on local air quality: A study in the context of uncommon airport operation - Hao Xu; Kai Xiao; Jun Pan; Qingyan Fu; Xiaodong Wei; Junrui Zhou; Yamei Yu; Xue Hu; Huarui Ren; Jinping Cheng; Shitao Peng; Ningning Hong; et al. (Journal of Environmental Sciences, 2023)

Occurrence, spatial distribution, and risk assessment of brominated flame retardants in farmland soils of typical provinces in China - Mabinty Sarah Tholley; Lartey Young George; Mengru Fu; Zhihua Qiao; Gehui Wang; Siyuan Ling; Cheng Peng; Wei Zhang; Chunmei Ye; Fang Liu; Jie Yang (Chemosphere, 2023)

Environmental fate of five brominated flame retardants co-exposure in a water-sediment-zebrafish microcosm system: Enrichment, removal, and metabolism mechanisms - Zhihua Qiao; Yawen Wang; Cong Lu; Siyuan Ling; Shanqi Zhou; Mengru Fu; Kailun Luo; Cheng Peng; Wei Zhang; Bingsheng Zhou (Journal of Cleaner Production, 2023)

Three-Dimensional Refined Modelling of Deep Structures by Using the Level Set Method: Application to the Zhaoping Detachment Fault, Jiaodong Peninsula, China - Jinli Wang; Xiancheng Mao; Cheng Peng; Jin Chen; Hao Deng; Zhankun Liu; Wensheng Wang; Zhengkai Fu; Chuntan Wang (Mathematical Geosciences, 2023)

Polyamide microplastics as better environmental vectors of Cr(VI) in comparison to polyethylene and polypropylene microplastics - Xuechun Shao; Qi Zhang; Weiyu Liang; Kailin Gong; Mengru Fu; Sadia Saif; Cheng Peng; Wei Zhang (Marine Pollution Bulletin, 2023)

Insight into a strategy to improve charge carrier migration in lead-free bismuth-based halide perovskite for efficient selective oxidation of thioanisole under visible light - Zihao Cui; Yaqiang Wu; Shuhui Zhang; Hui Fu; Guoqiang Chen; Zaizhu Lou; Xiaolei Liu; Qianqian Zhang; Zeyan Wang; Zhaoke Zheng; Hefeng Cheng; Yuanyuan Liu; et al. (Chemical Engineering Journal, 2023)

Exopolysaccharides from Lactobacillus plantarum reduces cadmium uptake and mitigates cadmium toxicity in rice seedlings - Kun-tai Li; Shuai-ying Peng; Bao Zhang; Wei-fu Peng; Shui-jing Yu; Xin Cheng (World Journal of Microbiology and Biotechnology, 2022)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Four sesquiterpenoids from the vegetable raw material Schisandra chinensis (Turcz.) Baill.: leaves and stems - Yong-Cheng Yang; Lu-Qi Liu; Kun-Jun Wang; Xue-Qing Zhang; San-Peng Fan; Xiao-Xu Gao; An-Hua Wang; Jing-Ming Jia; Chun-Wang Fu (Natural Product Research, 2022)

Application of regional citrate anticoagulation in patients at high risk of bleeding during intermittent hemodialysis: a prospective multicenter randomized controlled trial - Xiaoyan Tang; Dezheng Chen; Ling Zhang; Ping Fu; Yanxia Chen; Zhou Xiao; Xiangcheng Xiao; Weisheng Peng; Li Cheng; Yanmin Zhang; Hongbo Li; Kehui Li; et al. (Journal of Zhejiang University-SCIENCE B, 2022)

Horizontal and vertical heterogeneity of sediment microbial community in Site F cold seep, the South China Sea - Xinyi Zhai; Xiaochong Shi; Haojin Cheng; Peng Yao; Bin Zhao; Lin Chen; Jiwen Liu; Lei Cao; Minxiao Wang; Lulu Fu; Xiao-Hua Zhang; Min Yu (Frontiers in Marine Science, 2022)
Site F is the most vigorous cold seep known on the continental slope of the northern South China Sea. Up to now, the microbial community structures in sediments of Site F based on the high-throughput sequencing of the 16S rRNA genes have been studied extensively. However, few studies investigated the microbial community structures at fine vertical scales of Site F and control stations outside Site F. In this study, a comprehensive investigation of microbial communities in sediments of Site F along the depths varying from 0 to 24 cm below sea floor (cmbsf) of four sampling sites—SRS (Southern Reduced Sediment), NRS (Northern Reduced Sediment), Control 1 (close to Site F), and Control 2 (far from Site F)—was carried out. The high relative abundances of anaerobic methanotrophic archaea (ANME), Desulfobacterota [sulfate-reducing bacteria (SRB)], and Campylobacteria [sulfur-oxidizing bacteria (SOB)] in SRS and NRS indicated that these two sites were newborn cold seep sites compared with non-seep sites, Control 1, and Control 2. A positive correlation between ANME-1b, ANME-2, and SEEP-SRB and an enrichment of Sulfurovum and Methlomonadaceae were found in the surface sediments of both SRS and NRS, indicating that the processes of anaerobic oxidation of methane (AOM), sulfur oxidation, and sulfate reduction might occur in seep sites. SRS was enriched with ANME-1b and SEEP-SRB2 with a proposed sulfate-methane transition zone (SMTZ) approximately located at 8 cmbsf. The high abundance of ANME in SRS may due to the high concentration of methane. NRS was enriched with ANME-2, Desulfatiglans , Sulfurovum , and Methanosarcinaceae with a proposed SMTZ at about 10 cmbsf. According to the analyses of microbial community structure and environmental factors, NRS could be described as a notable cold seep reduced sediment site with low sulfate and high H 2 S that nourished abundant SEEP-SRB1, ANME-2, Methanosarcinales , and Sulfurovum , which showed similar distribution pattern. Our study expands the current knowledge on the differences of microbial communities in cold seep sites and non-seep sites and sheds light on the horizontal and vertical heterogeneity of sediment microbial community in Site F.

Effects of tidal variations on total nitrogen concentration, speciation, and exchange flux in the Shuidong Bay coastal water, South China Sea - Peng Zhang; Weisheng Luo; Miaojian Fu; Jibiao Zhang; Mingyue Cheng; Jiale Xie (Frontiers in Marine Science, 2022)
Nitrogen (N) plays an important role in marine ecosystems as a biogenic element for phytoplankton. The tidal cycle had major influence on various biogeochemical parameters of the bay and changed nutrients input with the ebb and flow of the tide. In this study, we collected samples from Shuidong Bay (SDB) in China, in August 2021, to explore the periodic variations in coastal waters during spring and neap tides. The effects of spring and neap tides on different speciation of nitrogen in the SDB and the exchange fluxes between the SDB and the South China Sea (SCS) were investigated. The results indicated that the concentrations of particulate nitrogen (PN) and N-NO 2 - were significantly different between the spring and neap tides ( P < 0.05). The total nitrogen (TN) concentrations in SDB during the spring and neap tides were 258.12 ± 89.49 μmol/L and 231.77 ± 56.86 μmol/L. During the spring and neap tides, total dissolved nitrogen (TDN) accounted for 54.1% and 52.2% of TN, respectively. In addition, dissolved organic nitrogen (DON) accounted for 81.4% and 69.9% of the TDN during the spring and neap tides, respectively. Furthermore, the net exchange fluxes of different speciation of nitrogen showed that the net exchange fluxes of TN were transported from SDB to SCS during the spring and neap tide, with the net exchange fluxes of 37.7 t and 8.8 t, respectively. The net exchange flux of TN during spring tide was 4.3 times higher than that of neap tide. In addition, a significant negative correlation was observed between dissolved inorganic nitrogen (DIN) and salinity in SDB during the spring and neap tides ( P < 0.001 ), indicated that DIN was mainly influenced by terrestrial sources inputs. A significant positive correlation ( P < 0.01 ) was observed between PN and Chlorophyll- a in SDB during the spring and neap tides, implied that the assimilation of a large number of planktonic organisms promoted PN formation. The present results revealed that tidal variation played an important role in regulating N speciation and exchange flux in coastal waters, which had great implications for N biogeochemistry and water quality improvement in SDB.

Biomechanical Analysis of the External Fixation in a Lumbar Fracture Model: A Finite Element Study - Yijia Liao; Yiguo Yan; Yu Kang; Wenjun Wang; Xizheng Song; Wen Peng; Haibin Fu; Huarong Chen; Cheng Wang (Journal of Medical and Biological Engineering, 2022)
Purpose This study aimed to investigate the biomechanical characteristics of the external spinal fixation for treating lumbar fracture through finite element analysis (FEA) and provide a theoretical basis for its further application. Methods Two different models of L3 fracture fixed with the external spinal fixation and the internal fixation system respectively were constructed. The ROM, maximum stresses at L3, and the screws of the two models were measured under load control. Subsequently, the applied torque, the maximum stressed at L3, L1/2, L2/3, L3/4, L4/5 discs and the screws were analyzed under displacement control. Results Under load control, the external fixation model reserved more ROM than the internal fixation model (40.4–48.0% vs 30.5–41.0%). Compared to the internal fixation model, the maximum stresses at L3 and screws in the external fixation model were increased. Under displacement control, the external fixation model required fewer moments (N·mm) than the internal fixation model (flexion: 7500 vs 12,294; extension: 7500 vs 9027). Further, the maximum stresses at L3 and the screws in the external fixation model were greater than those of the internal fixation model, while the maximum stresses at the upper and lower adjacent discs of fixed segments were less than the internal fixation model. Conclusion Compared to the internal fixation system, the external fixation has a better stress distribution with the greater overall mobility. It theoretically reduces the stress concentration of the adjacent discs and the stress shielding of the fractured vertebral body.

A Review on Hydraulic Fracture Height Growth for Layered Formation - Peng Tan; Jiawei Kao; Fushan Cheng; Yiliu Sun; Shihao Fu; Lejia Ren (Geotechnical and Geological Engineering, 2022)

An Improved Discontinuous Deformation Analysis to Solve Numerical Creep Problem in Shear Direction - Pengcheng Yu; Xinyan Peng; Yingbin Zhang; Dejian Li; Haiying Fu; Yin Cheng (Rock Mechanics and Rock Engineering, 2022)

Infestation and distribution of mites on the Yunnan red-backed vole (Eothenomys miletus) in Yunnan Province of southwest China between 2001 and 2015 - Rong Xiang; Xian-Guo Guo; Tian-Guang Ren; Cheng-Fu Zhao; Rong Fan; Zhi-Wei Zhang; Ke-Yu Mao; Pei-Ying Peng; Xiao-Bin Huang; Ti-Jun Qian (Biologia, 2022)

Reconciling the inconsistency of annual temperature cycles modelled from Landsat and MODIS LSTs through a percentile approach - Huyan Fu; Zhenfeng Shao; Peng Fu; Wenfeng Zhan; Yanhua Xie; Tao Cheng (International Journal of Remote Sensing, 2021)

RDF for temporal data management – a survey - Fu Zhang; Zhiyin Li; Dunhong Peng; Jingwei Cheng (Earth Science Informatics, 2021)

Short-term effects of ambient temperature on preterm birth: a time-series analysis in Xuzhou, China - Peng Cheng; Lei Peng; Jingwen Hao; Sha Li; Chao Zhang; Lianjie Dou; Weinan Fu; Fan Yang; Jiahu Hao (Environmental Science and Pollution Research, 2021)

The Effect of Atractylodes macrocephala Polysaccharides on Rabbit’s Host Defense Peptide (RSRAH) mRNA Expression - Guihua Fu; Yang Zhang; Yinglun Li; Xing He; Xiaofen Li; Peng Cheng; Hongwei Chen (International Journal of Peptide Research and Therapeutics, 2020)

Climate Variability Patterns and Their Ecological Effects on Ecosystems in the Northwestern North Pacific - Shuyang Ma; Yongjun Tian; Jianchao Li; Haiqing Yu; Jiahua Cheng; Peng Sun; Caihong Fu; Yang Liu; Yoshiro Watanabe (Frontiers in Marine Science, 2020)

Lacustrine record from the eastern Tibetan Plateau associated with Asian summer monsoon changes over the past ~ 6 ka and its links with solar and ENSO activity - Guodong Ming; Weijian Zhou; Peng Cheng; Hong Wang; Feng Xian; Yunchong Fu; Shugang Wu; Hua Du (Climate Dynamics, 2020)

Two-Year Observation of Fossil Fuel Carbon Dioxide Spatial Distribution in Xi’an City - Xiaohu Xiong; Weijian Zhou; Shugang Wu; Peng Cheng; Hua Du; Yaoyao Hou; Zhenchuan Niu; Peng Wang; Xuefeng Lu; Yunchong Fu (Advances in Atmospheric Sciences, 2020)

Plastic pollution in croplands threatens long‐term food security - Dan Zhang; Ee Ling Ng; Wanli Hu; Hongyuan Wang; Pablo Galaviz; Hude Yang; Wentao Sun; Chongxiao Li; Xingwang Ma; Bin Fu; Peiyi Zhao; Fulin Zhang; et al. (Global Change Biology, 2020)
Plastic pollution is a global concern given its prevalence in aquatic and terrestrial ecosystems. Studies have been conducted on the distribution and impact of plastic pollution in marine ecosystems, but little is known on terrestrial ecosystems. Plastic mulch has been widely used to increase crop yields worldwide, yet the impact of plastic residues in cropland soils to soil health and crop production in the long term remained unclear. In this paper, using a global meta‐analysis, we found that the use of plastic mulch can indeed increase crop yields on average by 25%–42% in the immediate season due to the increase of soil temperature (+8%) and moisture (+17%). However, the unabated accumulation of film residues in the field negatively impacts its physicochemical properties linked to healthy soil and threatens food production in the long term. It has multiple negative impacts on plant growth including crop yield (at the mean rate of −3% for every additional 100 kg/ha of film residue), plant height (−2%) and root weight (−5%), and soil properties including soil water evaporation capacity (−2%), soil water infiltration rate (−8%), soil organic matter (−0.8%) and soil available phosphorus (−5%) based on meta‐regression. Using a nationwide field survey of China, the largest user of plastic mulch worldwide, we found that plastic residue accumulation in cropland soils has reached 550,800 tonnes, with an estimated 6%–10% reduction in cotton yield in some polluted sites based on current level of plastic residue content. Immediate actions should be taken to ensure the recovery of plastic film mulch and limit further increase in film residue loading to maintain the sustainability of these croplands.

Association between long-term occupational manganese exposure and bone quality among retired workers - Defu Li; Xiaoting Ge; Zhenfang Liu; Lulu Huang; Yanting Zhou; Peng Liu; Lian Qin; Suzhen Lin; Chaoqun Liu; Qingzhi Hou; Longman Li; Hong Cheng; et al. (Environmental Science and Pollution Research, 2020)

African Orphan Crops Consortium (AOCC): status of developing genomic resources for African orphan crops - Prasad S. Hendre; Samuel Muthemba; Robert Kariba; Alice Muchugi; Yuan Fu; Yue Chang; Bo Song; Huan Liu; Min Liu; Xuezhu Liao; Sunil Kumar Sahu; Sibo Wang; et al. (Planta, 2019)

Population Genetics of Calotropis gigantea, a Medicinal and Fiber Resource Plant, as Inferred from Microsatellite Marker Variation in two Native Countries - Md. Rabiul Islam; Zhi-Zhong Li; Andrew W. Gichira; Mohammad Nur Alam; Peng-Cheng Fu; Guang-Wan Hu; Qing-Feng Wang; Ling-Yun Chen (Biochemical Genetics, 2019)

Anticancer effect of Polyphyllin Ι in colorectal cancer cells through ROS-dependent autophagy and G2/M arrest mechanisms - Si Yu; Lijiao Wang; Zhixing Cao; Daoyin Gong; Qianyi Liang; Hanting Chen; Huizhu Fu; Wenwen Wang; Xue Tang; Zihao Xie; Yang He; Cheng Peng; et al. (Natural Product Research, 2018)

Atmospheric fossil fuel CO2 traced by 14CO2 and air quality index pollutant observations in Beijing and Xiamen, China - Zhenchuan Niu; Weijian Zhou; Xue Feng; Tian Feng; Shugang Wu; Peng Cheng; Xuefeng Lu; Hua Du; Xiaohu Xiong; Yunchong Fu (Environmental Science and Pollution Research, 2018)

Using a global reference sample set and a cropland map for area estimation in China - Le Yu; XueCao Li; CongCong Li; YuanYuan Zhao; ZhenGuo Niu; HuaBing Huang; Jie Wang; YuQi Cheng; Hui Lu; YaLi Si; ChaoQing Yu; HaoHuan Fu; et al. (Science China Earth Sciences, 2017)

The Regulatory Roles of ncRNA Rli60 in Adaptability of Listeria monocytogenes to Environmental Stress and Biofilm Formation - Ye-long Peng; Qing-ling Meng; Jun Qiao; Kun Xie; Cheng Chen; Tian-li Liu; Zheng-xiang Hu; Yu Ma; Xue-peng Cai; Chuang-fu Chen (Current Microbiology, 2016)

Sunfleck limits the small-scale distribution of endangered Kingdonia uniflora in the natural habitat of subalpine forest proved by its photosynthesis - Chen-Guang Zhang; Xiao Liu; Yi-Lei Fan; Mao Wang; Yong-Fu Chai; Peng-Cheng Wan; Ya-Min Wang; Ming Yue (Acta Physiologiae Plantarum, 2016)

Metabolic differences of industrial acarbose-producing Actinoplanes sp. A56 under various osmolality levels - Kun-tai Li; Wei-fu Peng; Wei Xia; Lin Huang; Xin Cheng (World Journal of Microbiology and Biotechnology, 2016)

The spatial distribution of fossil fuel CO2 traced by Δ14C in the leaves of gingko (Ginkgo biloba L.) in Beijing City, China - Zhenchuan Niu; Weijian Zhou; Xiaoshan Zhang; Sen Wang; Dongxia Zhang; Xuefeng Lu; Peng Cheng; Shugang Wu; Xiaohu Xiong; Hua Du; Yunchong Fu (Environmental Science and Pollution Research, 2016)

Clipping alters the response of biomass production to experimental warming: A case study in an alpine meadow on the Tibetan Plateau, China - Gang Fu; Wei Sun; Cheng-Qun Yu; Xian-Zhou Zhang; Zhen-Xi Shen; Yun-Long Li; Peng-Wan Yang; Nan Zhou (Journal of Mountain Science, 2015)

MiR-218-targeting-Bmi-1 mediates the suppressive effect of 1,6,7-trihydroxyxanthone on liver cancer cells - Wei-Ming Fu; Li-Peng Tang; Xiao Zhu; Ying-Fei Lu; Yan-Ling Zhang; Wayne Yuk-Wai LEE; Hua Wang; Yang Yu; Wei-Cheng Liang; Chun-Hay Ko; Hong-Xi Xu; Hsiang-Fu Kung; et al. (Apoptosis, 2015)

Detection and Characterization of Avastrovirus Associated with Diarrhea Isolated from Minks in China - Na Sun; Yong Yang; Gui-Sheng Wang; Xi-Qun Shao; Shu-Qin Zhang; Feng-Xue Wang; Bin Tan; Fu-Lin Tian; Shi-Peng Cheng; Yong-Jun Wen (Food and Environmental Virology, 2014)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

Response of ecosystem respiration to experimental warming and clipping at daily time scale in an alpine meadow of tibet - Gang Fu; Zhen-xi Shen; Xian-zhou Zhang; Cheng-qun Yu; Yu-ting Zhou; Yun-long Li; Peng-wan Yang (Journal of Mountain Science, 2013)

Finer resolution observation and monitoring of global land cover: first mapping results with Landsat TM and ETM+ data - Peng Gong; Jie Wang; Le Yu; Yongchao Zhao; Yuanyuan Zhao; Lu Liang; Zhenguo Niu; Xiaomeng Huang; Haohuan Fu; Shuang Liu; Congcong Li; Xueyan Li; et al. (International Journal of Remote Sensing, 2013)

Spermidine affects the transcriptome responses to high temperature stress in ripening tomato fruit - Lin Cheng; Rong-rong Sun; Fei-yan Wang; Zhen Peng; Fu-ling Kong; Jian Wu; Jia-shu Cao; Gang Lu (Journal of Zhejiang University-SCIENCE B, 2012)

A recessive gene controlling male sterility sensitive to short daylength/low temperature in wheat (Triticum aestivum L.) - Xiao-dong Chen; Dong-fa Sun; De-fu Rong; Jun-hua Peng; Cheng-dao Li (Journal of Zhejiang University-SCIENCE B, 2011)

Emerging threat of thrips-borne Melon yellow spot virus on melon and watermelon in Taiwan - Jui-Chu Peng; Shyi-Dong Yeh; Li-Hsin Huang; Ju-Ting Li; Yuan-Fu Cheng; Tsung-Chi Chen (European Journal of Plant Pathology, 2011)

Genomic sequence of an avian paramyxovirus type 1 strain isolated from Muscovy duck (Cairina moschata) in China - S.-H. Shi; Yu Huang; S.-J. Cui; L.-F. Cheng; G.-H. Fu; X. Li; Z. Chen; C.-X. Peng; F. Lin; J.-S. Lin; Jing-Liang Su (Archives of Virology, 2011)

SCAR Makers and Multiplex PCR-Based Rapid Molecular Typing of Lentinula edodes Strains - Xueqian Wu; Haibo Li; Weiwei Zhao; Lizhong Fu; Huazheng Peng; Liang He; Junwen Cheng; Hailong Wei; Qingqi Wu (Current Microbiology, 2010)

Trade-offs between constitutive and induced resistance in wild crucifers shown by a natural, but not an artificial, elicitor - Peng-Jun Zhang; Jin-Ping Shu; Cheng-Xin Fu; Yun Zhou; Ying Hu; Myron P. Zalucki; Shu-Sheng Liu (Oecologia, 2008)

Essential oil of Actinidia macrosperma, a catnip response kiwi endemic to China - Yun-peng Zhao; Xiao-yun Wang; Zhi-can Wang; Yin Lu; Cheng-xin Fu; Shao-yuan Chen (Journal of Zhejiang University-SCIENCE B, 2006)

Dissection of cry Gene Profiles of Bacillus thuringiensis Isolates in Taiwan - Fu-Chu Chen; Ming-Chu Tsai; Cheng-Hung Peng; Kin-Fu Chak (Current Microbiology, 2004)

Synthesis, structure and anti-acetylcholinesterase activity of 4β-methoxymethyl-4β-demethyl territrem B - Fu-Chuo Peng; Jur-Shan Cheng (Mycopathologia, 1997)